Random and Directed Movement by Warren Root Collar Weevils (Coleoptera: Curculionidae), Relative to Size and Distance of Host Lodgepole Pine Trees. Issue 4 (24th July 2020) - Balogh, Sharleen L; Björklund, Niklas; Huber, Dezene P W; Lindgren, B Staffan
Abstract: Hylobius warreni Wood (Coleoptera: Curculionidae) is a pest of conifers, especially lodgepole pine ( Pinus contorta var. latifolia Douglas ex Loudon) (Pinales: Pinaceae) in the Interior of British Columbia. The larvae feed on the roots and root collars and cause girdling damage, resulting in mortality or growth reductions. Previous research has suggested the adult weevils locate potential host trees by using random movements and vision, but likely not chemosensory cues. The purpose of this study is to determine if adult H. warreni respond to particular tree characteristics versus encounter potential hosts at random. Study A was a capture–mark–recapture experiment where weevils were captured on mature pine trees, while Study B was a tracking experiment within a young pine plantation. Weevils showed a preference for larger trees, and for trees that were closer to the weevil's last known location. In Study A, weevils also avoided climbing trees in poor health, while in Study B, the weevils' preference for taller trees increased as their distance from the weevil increased, as well as when taller trees were closer to other trees. Movement rates were similar to those observed in previous studies, were positively correlated with the average spacing of trees, and declined with time after release. This confirms previous findings that H. warreni may locate host trees by both vision and random movements, and that their movements are determined primarily by the size and distribution of potential host trees within their habitat.